Auditing an MRP System - Cox, James F.; Zmud, Robert W.; Clark, Steven J. (Academy of Management Journal, 1981)
Although material requirements planning (MRP) has become an increasingly popular approach to production scheduling and control, few systems are considered successful. This research presents a simplified conceptual model for information system implementation success, an auditing instrument to evaluate the effectiveness of an MRP system, and a case study illustrating the use of the instrument.